2011
DOI: 10.1099/vir.0.031526-0
|View full text |Cite
|
Sign up to set email alerts
|

p38 mitogen-activated protein kinase is crucial for bovine papillomavirus type-1 transformation of equine fibroblasts

Abstract: Equine sarcoids represent the most common skin tumours in equids worldwide, characterized by extensive invasion and infiltration of lymphatics, rare regression and high recurrence after surgical intervention. Bovine papillomavirus type-1 (BPV-1) and less commonly BPV-2 are the causative agents of the diseases. It has been demonstrated that BPV-1 viral gene expression is necessary for maintaining the transformation phenotype. However, the underlying mechanism for BPV-1 transformation remains largely unknown, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…E5 and E6 induce the over-expression of p38 mitogen-activated protein kinase (MAPK) which in turn leads to phosphorylation of an AP-1 component (Fra-1), triggering MMP-1 expression. Both increased proliferation and invasiveness were shown to be mediated by MAPK [40]. The MAPK-AP-1-MMP-1 signalling cascade was thus shown to be involved in the invasiveness of equine sarcoid fibroblasts.…”
Section: Bpv-induced Cell Transformationmentioning
confidence: 92%
“…E5 and E6 induce the over-expression of p38 mitogen-activated protein kinase (MAPK) which in turn leads to phosphorylation of an AP-1 component (Fra-1), triggering MMP-1 expression. Both increased proliferation and invasiveness were shown to be mediated by MAPK [40]. The MAPK-AP-1-MMP-1 signalling cascade was thus shown to be involved in the invasiveness of equine sarcoid fibroblasts.…”
Section: Bpv-induced Cell Transformationmentioning
confidence: 92%
“…AP-1 is crucial for cellular invasion (Malliri et al, 1998;Ozanne et al, 2007), and inhibition of AP-1 activity can block cell invasion and metastasis (Leaner et al, 2009). In our recent study (Yuan et al, 2011b), we found that p-Fra-1 expression was associated with p38 MAPK activity, and that inhibition of p38 by the inhibitor SB203580 caused abolition of p-Fra-1 expression, a significant decrease in MMP-1 expression and reversion of the transformed phenotype of equine fibroblasts. This finding supports the necessity of AP-1 for the stimulation of MMP-1 and the transformation of equine fibroblasts by BPV-1.…”
Section: Discussionmentioning
confidence: 99%
“…These experiments also demonstrated that transformation required PDGF β receptor kinase activity (Drummond-Barbosa et al, 1995). In addition, transformation of fibroblasts was blocked by pharmacologic inhibition of PDGF receptor enzymatic activity or by genetic manipulations that inhibited expression or activity of the PDGF β receptor or its signaling pathway (Figure 5) (Klein et al, 1998; Lai, Edwards, and DiMaio, 2005; Petti and Ray, 2000; Riese and DiMaio, 1995; Yuan et al, 2011a; Yuan et al, 2011b). …”
Section: Fibropapillomavirus E5 Proteinsmentioning
confidence: 99%